2018
DOI: 10.1007/s11033-018-4265-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor 7-like 2 single nucleotide polymorphisms are associated with lipid profile in the Balinese

Abstract: Transcription factor 7-like 2 (TCF7L2) protein plays an important role in glucose and lipid metabolisms. Single nucleotide polymorphisms (SNPs) in the TCF7L2 gene contribute to increased fasting plasma glucose (FPG) and body mass index (BMI), and altered lipid concentrations in various population. We investigated whether the TCF7L2 SNPs were associated with obesity, high FPG and altered lipid profile in the Balinese. A total of 608 Balinese from rural and urban Bali, Indonesia, were recruited. Triglycerides (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Therefore, the significant association between TCF7L2 SNPs with TC might occur due to its major influence on LDL-C. A study performed using MetS subject from eight European countries have reported that rs290481 C allele, the major allele in that population, also contributed to higher LDL-C levels ( Delgado-Lista et al, 2010 ). Our previous study had also reported the associations of three TCF7L2 SNPs (rs7903146, rs12255372, rs10885406) with elevated TC/HDL-C ratio ( Oktavianthi et al, 2018 ). TC levels was known to be increased primarily due to elevated LDL-C levels ( Kreisberg & Kasim, 1987 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the significant association between TCF7L2 SNPs with TC might occur due to its major influence on LDL-C. A study performed using MetS subject from eight European countries have reported that rs290481 C allele, the major allele in that population, also contributed to higher LDL-C levels ( Delgado-Lista et al, 2010 ). Our previous study had also reported the associations of three TCF7L2 SNPs (rs7903146, rs12255372, rs10885406) with elevated TC/HDL-C ratio ( Oktavianthi et al, 2018 ). TC levels was known to be increased primarily due to elevated LDL-C levels ( Kreisberg & Kasim, 1987 ).…”
Section: Discussionmentioning
confidence: 90%
“…These findings indicated a relationship between TCF7L2 and dyslipidemia. However, the minor allele frequencies of these three SNPs were rather low in Balinese, and thus they were hard to detect ( Oktavianthi et al, 2018 ). Therefore, in the present study, we investigated the associations of other TCF7L2 intronic SNPs, rs290487 (C > T, intron 8) ( NCBI, 2021a ) and rs290481 (C > T, intron 16) ( NCBI, 2021b ), which have higher allele frequencies in East-Asian (MAF > 0.60).…”
Section: Introductionmentioning
confidence: 99%
“…The rs7903146 T-allele has been positively associated with risk for T2DM in European, 23 Indian, Thai, 24 and Iranian populations, 25 East Asian populations, namely, Japanese 26 and Chinese, 27 Turks, 28 Arabic, and Algerian, 29 African, 30 Brazilian, 31 and African American populations. 32 However, conflicting results have been reported in some studies in populations from China, Indonesia, 33 Saudi Arabia, and the United Arab Emirates, 34 Egypt, 35 as well as in a Native American population of North America, African Americans, Brazilian, 18 and Afro Caribbeans. 23 So far, the data suggest that the allelic frequencies of the rs7903146 SNP and possibly, the effect size of this SNP are variable worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study enrolling 612 participants from five locations (286 female and 326 male) in Bali Province, Indonesia, was conducted in 2008-2015 with written informed consent (Malik et al, 2011;Suastika et al, 2011b;Oktavianthi et al, 2012Oktavianthi et al, , 2018 Manuscript to be reviewed tissue (Swainson et al, 2017). The high BMI (BMI ≥25 kg/m 2 ) and high WC (male ≥ 90 cm; female ≥ cm) cut offs were according to the Asia-Pacific perspective redefining obesity in adult Asian, while the high WHtR cut off at ≥ 0.5 was based on previous reports (Lee et al, 1995;Hsieh & Yoshinaga, 1995; WHO Regional Office for the Western Pacific, 2000).…”
Section: Subjects Study Design Measurementsmentioning
confidence: 99%